A comprehensive review of training methods for physical demands in adolescent tennis players: a systematic review - Guo, Yuxin; Xie, Jia; Dong, Gengxin; Bao, Dapeng (Frontiers in Physiology, 2024)
Background: Adolescent tennis players encounter critical physical demands, but the lack of comprehensive analysis of training types hampers the selection of optimal training programs. This study aims to conduct a systematic literature review to analyze the effectiveness and limitations of various training types on the physical demands of adolescent tennis players, summarizing the optimal training methods to enhance these physical qualities. Methods: From March 2024, a comprehensive search was conducted across four electronic databases: SCOPUS, PubMed, EBSCOhost (SPORTDiscus), and Web of Science. Additionally, Google Scholar and other sources of gray literature were referenced. Original research articles with an experimental design were included. The methodological quality of the included studies was evaluated using the Physiotherapy Evidence Database (PEDro) scale, and the overall scientific evidence was determined through the best evidence synthesis (BES). Results: Eighteen articles on exercise training met all inclusion criteria and were included in this systematic review. These studies maintained a high standard of quality, making their findings relatively credible. Among them, five studies investigated plyometric training, five focused on neuromuscular training, three explored functional training, two examined traditional strength training, and three assessed High-Intensity Interval Training. Conclusions: To enhance speed, strength, power, agility, and dynamic balance, it is recommended to prioritize plyometric training, neuromuscular training, and functional training over traditional tennis training. Functional training is particularly effective for improving flexibility and balance, while plyometric training is more suited for increasing power and speed. Neuromuscular training, when performed before routine workouts, is beneficial for enhancing speed, flexibility, and strength. Hard surface training is ideal for boosting power, whereas sand training excels in improving strength, speed, and balance. Combining HIIT with strength training is especially advantageous for enhancing short-distance sprinting, repeated sprint ability, and power. By appropriately combining and utilizing these training methods, the physical capabilities and sports performance of adolescent tennis players can be comprehensively optimized.